Imagens da diferença: artes visuais e diversidade sexual no ensino fundamental - Pereira, Alexandre Adalberto (2013)
This study was developed with Arts Educator who works in Basic Education in the Municipal Schools in the City of Uberlândia, Minas Gerais, Brazil. These teachers participated, in 2012, in meetings of continued training offered by Centro de Estudos e Projetos Educacionais Julieta Diniz CEMEPE. The Problem pursues recognize how these teachers constructed knowledge about sexual diversity in their classrooms. The general objective of this Doctorate Investigation is to understand and register the discourses of these teachers of Visual Arts about sociocultural structures that prevent or empower the development of educational actions in Arts, focused on sexual diversity in the classroom. Therefore are proposed the following specific objectives: A) analyze, from the theoretical perspective of visual culture, discourses measured by those teachers, the interconnections between the art education and sexual diversity; B) understanding from the viewpoint of these teachers, aspects of their initial and continuing formation that enable the construction of knowledges of sexual diversity; C) Consideration the narratives of these teachers how they constructed discourses about sexual diversity in schools. The methodological orientation was qualitative with the intention to understanding the universe of meanings of the group concerned about the topic of sexual diversity in schools. The method of collecting data was the focus group as a form of promoting an open and flexible discussion with the participants about the topic. In this thesis I use the theoretical bases of Visual Culture that follows a non-hierarchical and inclusive discourse between texts and images, understanding that human experiences, in contemporary, are mediated by visual artifacts coming from various cultural sources. In this perspective, the production of meanings for the images is directly related to the relations of power and knowledge. The analysis of data is guided by theoretical construcionist as reference on sexuality that is discussed in the Foucaultian perspective to offer understanding of institutional dimension, historical and constructive about the sexuality as a social and cultural phenomenon of modernity.